Two-stage distributionally robust strategic offering in pool-based coupled electricity and gas market. (15th February 2023) - Wang, Cheng; Sayed, Ahmed Rabee; Zhang, Han; Zhang, Xian; Ren, Jianpeng; Jia, Qiyue; Bi, Tianshu
Abstract: The intensified interactions between power and gas systems and the wide utilization of renewable energy introduce additional challenges in energy marketing and pricing mechanisms. Existing studies either neglect energy uncertainties in deterministic market-clearing models, use predetermined strategic offering prices in single-level models, or approximate gas dynamics in nonrealistic models. This paper proposes a bi-level two-stage distributionally robust electricity–gas market clearing (EG-MC) model considering energy uncertainties and strategic offering prices from energy producers. Strategic energy producers submit their offering prices in the upper-level problem to the EG-MC operator, who maximizes market profits under the realizations of renewable energy outputs while balancing the robustness and conservativeness of the day-ahead market decisions. The presence of gas dynamics in the two stages of the decision-making framework generates an intractable EG-MC problem. A novel triple-loop procedure, namely inner and outer columns & constraints generation and bilinear approximation algorithms, is proposed to sufficiently solve the formulated model. Finally, numerical analyses on an EG-MC model demonstrate the effectiveness of the distributionally robust strategic offers and the performances of the solution methodology. Graphical abstract: Highlights: A bi-level two-stage DRO model for electricity-gas markets is proposed. Energy uncertainties, offering prices, and gas dynamics are formulated. A novel triple-loop procedure with high computational performances is proposed. The merits of the DRO-based strategic offers and the methodology are validated.